Help !!!
See question in image.
Please show workings .
![Help See question in imagePlease show workings class=](https://us-static.z-dn.net/files/d75/68c72262493de55c46535b8f39dbbd92.jpg)
Answer:
[tex]\frac{dy}{dx}[/tex] = 2x + 3
Step-by-step explanation:
The gradient function is the derivative [tex]\frac{dy}{dx}[/tex]
Differentiate using the power rule
[tex]\frac{d}{dx}[/tex] (a[tex]x^{n}[/tex] ) = na[tex]x^{n-1}[/tex] and [tex]\frac{d}{dx}[/tex] ( constant ) = 0
Given
y = x² + 3x + 1, then
[tex]\frac{dy}{dx}[/tex] = 2[tex]x^{2-1}[/tex] + 3[tex]x^{1-1}[/tex] + 0 = 2x + 3[tex]x^{0}[/tex] = 2x + 3 ← gradient function